2012
DOI: 10.17305/bjbms.2012.2509
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a potent antibiotic producer bacterium, especially against MRSA, from northern region of the Persian Gulf

Abstract: Nowadays, emergence and prevalence of MRSA (Methicillin Resistant Staphylococcus aureus) strain have become a great global concern in  st century, so, it is necessary to discover new antibiotics against this pathogen. Th e aim of this study was isolation and evaluation marine bacteria from the Persian Gulf in order to fi nding antibiotic compounds against some pathogenic bacteria. For this purpose, water and sediment samples were collected from the Persian Gulf during March to October . Th e antibacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
2
11
1
Order By: Relevance
“…The highest number of antibiotic producing isolate was B. subtilis (40.09%) and the least number of antibiotic producing isolate belonged to the species B. circulans (4.54%). This result is contrasting to a study carried out in soil of marine environment where antibiotic producers of genus Bacillus were all identified as B. subtilis (21). The highest number of antibiotic producers were found in basic soil (45.45%) whereas the least were found in acidic soil (13.6%).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The highest number of antibiotic producing isolate was B. subtilis (40.09%) and the least number of antibiotic producing isolate belonged to the species B. circulans (4.54%). This result is contrasting to a study carried out in soil of marine environment where antibiotic producers of genus Bacillus were all identified as B. subtilis (21). The highest number of antibiotic producers were found in basic soil (45.45%) whereas the least were found in acidic soil (13.6%).…”
Section: Discussioncontrasting
confidence: 92%
“…In a study similar like this where the activity of the antibiotic producers was only tested against Gram positive bacteria, 5.88% showed antibacterial activity against Gram-positive bacteria, and also had good activity against MRSA (21). (Darabpour et al 2012 9.09% colonies had a broad spectrum activity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar cell wall effects have been reported in S. aureus treated with bacteria-derived antibiotics [24,25].…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies reported the isolation of anti-MRSA substances, especially from marine Pseudomonas species. Darabpour et al [26] collected the sediment samples from Persian Gulf and isolated the Pseudoalteromonas piscicida PG-01 showing potent anti-MRSA activity. Similarly, Pseudoalteromonas phenolica O-BC30 [7] and Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%